OPTIMIZATION OF DIAGNOSIS AND TREATMENT METHODS FOR PAINFUL DYSFUNCTION OF THE TEMPOROMANDIBULAR JOINT IN RHEUMATOID ARTHRITIS - Abdullaev Sharif Yuldashevich; Abdashimov Zafar Bakhtiyarovich; Bukharova Fotimakhon Khasanovna (Scholar Express Journals, 2025)
As a result of research by various authors, dentists have comprehensive data on the structure of temporomandibular joint (TMJ) elements. This statement emphasizes that the anatomical and functional features of the temporomandibular joint (TMJ) are well studied in dentistry. However, despite extensive knowledge about joint structure, the problem of diagnosing and treating its pathologies, especially in systemic diseases such as rheumatoid arthritis, remains relevant
Keywords: Temporomandibular joint; rheumatoid arthritis; painful dysfunction